THE IMPACT OF THE IMPLEMENTATION OF EMKM SAK AND ACCOUNTING UNDERSTANDING ON TAXPAYER COMPLIANCE IN MSMES - Mia Septiara Siringo Ringo; Dewinta Putri Ardana; Anna Siti Rahma; Anni Siti Rahmi; Muhammad Rahman (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
This study aims to analyze the effect of the Implementation of SAK EMKM and Accounting Understanding on Tax Compliance of UMKM. Indonesia is a country whose main source of income comes from taxes, but the realization of tax revenue until the end of September 2025 was recorded to have only reached 62.4% of the set target. UMKM have a strategic role in the economy, but many actors still have minimal understanding of accounting, thus facing challenges in financial reporting. Therefore, DSAK IAI established SAK EMKM with the aim of increasing transparency and accountability of entity financial reporting. The study population was all UMKM registered in Palmerah District (100 business units), with the sample determined using the Solvin formula. The variables of SAK EMKM Implementation (X1) and Accounting Understanding (X2) were tested for their simultaneous and partial effects on Taxpayer Compliance (Y). Data were collected through a questionnaire with a five-level Likert Scale. The results are expected to be positive and significant, because good accounting implementation will improve the accuracy of financial reports as a basis for calculating tax payable and encourage taxpayer willingness.